2011
DOI: 10.1016/j.jtcvs.2010.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and skills training in mitral valve surgery

Abstract: Simulation-based learning with formative feedback results in overall improved performance of simulated mitral annuloplasty. In complex surgical procedures, simulation may provide necessary early graduated training and practice. Importantly, a "passing" grade can be established for proficiency-based advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 18 publications
(31 reference statements)
0
60
0
Order By: Relevance
“…Several studies have documented resident skills improvement on coronary anastomosis and mitral valve simulators at a single institution [9,10]. Recorded video has become an important adjunct to assessment based on direct observation, and interrater reliability of video-based grading has been established among experienced CT surgeons [11].…”
mentioning
confidence: 99%
“…Several studies have documented resident skills improvement on coronary anastomosis and mitral valve simulators at a single institution [9,10]. Recorded video has become an important adjunct to assessment based on direct observation, and interrater reliability of video-based grading has been established among experienced CT surgeons [11].…”
mentioning
confidence: 99%
“…Conventional or open mitral valve repair is technically challenging, and investigators have reported the improvement in trainee performance after simulation training for open or conventional mitral valve surgery. 17 Because of this repeated-measures study design, the results may have been limited by subject fatigue after several trials, carry-over effects from one technique to the next, and the order of technique presentation. To minimize these effects, the order of trials with 2D and 3D visualization was randomized for each subject.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid coronary revascularization is also an option but the comparative effectiveness to both conventional CABG and multivessel stenting should be evaluated. Reliability of Skills Assessment in Cardiac Surgery Cardiac surgery simulation-based learning has been directed at technical skills training in small vessel anastomosis, beating heart surgery, and valve surgery (1)(2)(3)(4)(5)(6)(7). In the simulation laboratory, the trainee needs to demonstrate knowledge of anatomy,…”
mentioning
confidence: 99%
“…Such an approach permits creation of assessment tools based on principles of cognitive task analysis (1)(2)(3)(4)(5)7). In addition, for whole-task training, such as in crisis management, a computer-controlled, tissue-based simulator that simulates the entire cardiac procedure is employed (4,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation